The Spatial Transformation of the River Waterfront through Three Historical Periods: A Case Study of Belgrade - Branislava Simic (Journal of Contemporary Urban Affairs, 2020)
Urban renewal of the coastal area has regained importance in recent years. The main problem with the city's coastal area is often the insufficient utilization of its potential. The paper analyzes the process of urbanization and treatment of the waterfront through the three historical periods: 1. traditional city, 2. during Modernism and 3. contemporary urbanism. Belgrade is chosen as a case study because it is located on the banks of the two rivers the Sava and the Danube, and throughout history, rivers had a significant role in the urban development of the city. A polygon for the methodology of urban morphological research for this paper was the contrast between the Old Belgrade and traditional city core and the New Belgrade created on the principle of the modern movement in architecture. The paper aims to research the relationship between the city and the river waterfront by the method of compare spatial-temporal transformations and revealing the positive and negative elements of each period of urbanization. The result of the analysis indicates a changed treatment of the river waterfront through time - from the fortified city isolated from the river to the gradual descent of the city center near the coast.